Pendekatan Kasus Terindikasi Stunting dengan Media Handbook dan Poster di Desa Kare Kecamatan Kare Kabupaten Madiun - Diah Ika Rahayu; Farisya Nurliana Fatin; M Kharis Khamdan; Kartika Dewi Arifianti; Edra Ivannanda Hidayatullah; Yulis Setiya Dewi (Universitas Batanghari Jambi, 2023)
It is known that there are still many toddlers in Kare Village who are indicated as stunting. To perform anthropometry of toddlers and provide counseling to mothers of toddlers about stunting. Target selection refers to data obtained from the Kare Health Center based on the measurement results at the posyandu in February 2022. The Kare 3 KKN team sorted the data based on the closest working area, namely Teratai 7 Posyandu so that 4 toddlers were indicated to be stunting. The Community Service Team carried out anthropometry to toddlers in the form of measuring height and weight, as well as counseling to mothers of toddlers by door to door using a poster entitled